Aesthetics of New Age Chinese Cinematography - Shazhinbat A., Ishnorov K. (Current trends in the development of education system, 2022)
the following article is devoted to the development of cinematography in China. The authors offer the contemplation of journey which the Chinese cinematography undertook. Of peculiar significance to the work is the idea of different aesthetics, from “political cinema” to “ideological pictures”. To summarize the article, researchers underline the originality of Chinese cinema and its inseparability from the cultural identity of the nation.
Keywords: эстетика; aesthetics; китайский кинематограф; кино нового века в Китае; Chinese cinematography; new age cinema in China